Adaptation of MSME Actors to Technological Development During The Pandemic - Ngr. Putu Raka Novandra Asta; Ramadhani Kirana Putra; samsidar (Oikonomia : Journal of Management Economics and Accounting, 2024)
The COVID-19 pandemic has accelerated digital transformation in Indonesia's Micro, Small and Medium Enterprises (MSMEs) sector, which previously relied more on conventional methods. Social restrictions encourage MSME players to adapt to technology, especially in marketing and operational efficiency. This study aims to explore how MSMEs are adapting to digital technology during the pandemic, with a focus on marketing digitalization, the use of technology for operational efficiency, and challenges faced related to infrastructure and digital literacy. Using a descriptive qualitative approach and case studies with in-depth interviews with 10-15 MSME players, this research found that digital technology has become an important element in maintaining MSME business continuity. While the benefits of technology are clear, constraints such as limited infrastructure, low digital literacy, and investment costs are major barriers. Therefore, this study suggests the need for collaboration between the government, private sector, and educational institutions to provide training, more affordable access to technology, and better infrastructure to support MSME digitalization. The findings are expected to provide insights for policymakers and industry players in designing effective measures to accelerate the digital transformation of MSMEs, improve their competitiveness in the global market, and prepare them for future economic challenges